2008
DOI: 10.1007/s11920-008-0006-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric comorbidity and depression in older adults

Abstract: Late-life depression rarely occurs in isolation. Thus, screening for and assessment of late-life depression should always involve screening for other psychiatric disorders, including anxiety, personality disorders, and alcohol misuse. Comorbidity often makes treatment to relieve depressive symptoms more complicated, more comprehensive, and longer. Current late-life depression research indicates the strongest support for antidepressant medication and/or cognitive-behavioral therapy for comorbid anxiety, antidep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…This discrepancy can be explained by 1) older adults are less likely than younger people to report having mental problems in epidemiological surveys 20 ; 2) older adults may use psychotropics to relieve physical aliments; or 3) older adults tend to have a high probability of psychiatric comorbidities, indicating more severe conditions, which may require more psychotropics. 21 The decrease in use we found between 1983 and 1989 (8.38% to 7.44%) may be explained by a shift in the drug plan coverage from a first-dollar, cost-sharing arrangement with a fixed copayment, to a family-based deductible program in 1988. The dominant growth of psychotropic use in the late 1990s is consistent with numerous factors, including, that with more consistent home-based supports, patients tend to stay home longer, the "de-insurance" of light levels of care, 11 and the introduction of new medications.…”
Section: Discussionmentioning
confidence: 81%
“…This discrepancy can be explained by 1) older adults are less likely than younger people to report having mental problems in epidemiological surveys 20 ; 2) older adults may use psychotropics to relieve physical aliments; or 3) older adults tend to have a high probability of psychiatric comorbidities, indicating more severe conditions, which may require more psychotropics. 21 The decrease in use we found between 1983 and 1989 (8.38% to 7.44%) may be explained by a shift in the drug plan coverage from a first-dollar, cost-sharing arrangement with a fixed copayment, to a family-based deductible program in 1988. The dominant growth of psychotropic use in the late 1990s is consistent with numerous factors, including, that with more consistent home-based supports, patients tend to stay home longer, the "de-insurance" of light levels of care, 11 and the introduction of new medications.…”
Section: Discussionmentioning
confidence: 81%
“…Comorbidity of anxiety and depression are common and difficult to distinguish among older people (Gum & Cheavens, 2008). Other research suggests that in chronically ill, functionally impaired older adults, anxiety and depressive symptoms commonly co-occur ( r = 0.71; Petkus et al, 2010).…”
Section: Rationale For Act With Older Adultsmentioning
confidence: 99%
“…Patients usually report somatic complaints, hypochondria, insomnia, and apathy symptoms (lack of interest and motivation), but sadness, loss of hope and wreck are less frequent (Avery & Silverman, 1984;Brown et al, 1984). It is usual for depression to present co-morbidly with other psychiatric disorders such as anxiety, personality disorders and substance abuse (more frequently, alcohol) (Callahan et al, 1994;Gum & Cheavens, 2008;Speer & Bates, 1992). Several authors have found that reduced insight is not uncommon among these patients (Ghaemi et al, 2000;Yen et al, 2005).…”
Section: Late Onset Depressionmentioning
confidence: 99%